Reading the New Testament from a theological perspective - H. C. van Zyl (Acta Theologica)
This article argues that, from the perspective of the faith community, it is not enough to read the Bible only from a “technical” point of view; a theological perspective is also required. Subsequently the article deals with what a theological reading entails: A reader-orientated and a text-orientated view are presented.